REFLEKSI TERHADAP KEBIJAKAN SISTEM ZONASI DI PROVINSI RIAU TAHUN 2018-2019 - Difa Cucu Sabrina; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
PPDB zoning system is enforced in all cities in Indonesia, one of which is Pekanbaru City, Riau Province. PPDB is a school agenda that takes place every year and is guided by policy regulations set by the Government. Every year the implementation of PPDB causes different polemics according to the circumstances of each region. Enduring problems such as the lack of group numbers are the main cause of the unsuccessful implementation of PPDB at the SMA Negeri Pekanbaru City level. The purpose of the zoning system in implementing PPDB is to equal access to education services based on the principles of objectivity, transparency, accountability, and justice or non-discrimination. The research objective was to determine the evaluation of zoning system policies on PPDB in public high schools in Pekanbaru City which was carried out by the Riau Provincial Education Office based on 6 indicators of policy evaluation from William Dunn, namely effectiveness, efficiency, adequacy, fairness, responsiveness and accuracy.             The research method used in this research is descriptive research method with a qualitative approach. Data collection techniques through interviews, observation, and documentation study. The problem examined in this study is the PPDB policy of the zoning system in Pekanbaru City Public Senior High School which is carried out by the Riau Provincial Education Office based on the Riau Governor Regulation and the Regulation of the Ministry of Education and Culture of the Republic of Indonesia.             The results of this study indicate that the zoning system policy in Pekanbaru City is still not running according to its objectives, namely equal access to education services when viewed from the six indicators of policy evaluation. However, it has been implemented in accordance with policy principles, namely objective, transparent and accountable, but it is not just. This policy also has impacts that are expected and that are not as well as those that can be felt now and in the future. The hope in the future is that equal distribution of education quality can be realized immediately.  Keywords: Reflection, Zoning System Policy, Equitable Access to Education Services